Implementation of Al-Qur'an Reading Guidance for Students of the Bolon Islamic Boarding School, Tenajar Lor Village, Kertasemaya District, Indramayu Regency - M. Rizqi Abil Mawahib (Aslama: Journal of Islamic Studies, 2024)
Arabic Reading and Writing Guidance is the most important activity goal in religion as a form of how to read the Qur'an that has been revealed or sent down by God, as a guide for mankind and in reading and writing the Qur'an there are differences with what we can recognize with general writing such as formal and non-formal letters, while in the Qur'an are non-formal and formal letters, non-formal is Arabic writing such as Alif and Ba while formal is a and b c some people must be familiar with the name of the Koran in terms of the form of reading procedures are very different such as there are laws of nun mati, tanwan and tawin there are fatihah kasroh dlomah sukun etc. seen from the aspect of reading recognition alone there are those who know the name makrijul letters in memorizing the Qur'an measuring the ability of students. because the most common humans can read are formal letters because formal letters are legendary and many have been able to read formal letters. 1) find out whether there are students who memorize fluently around the Bolon Islamic Boarding School 2) find out the factors of not being able to memorize reading, writing and short letters in order to motivate students to actively study the Koran 3) find out the ability to memorize the Koran this study uses quantitative research with data collection steps through observation, documentation and interviews. The results of the study show that the majority of students at the Bolon Islamic Boarding School in Tenajar Lor Village are able to memorize the Koran and read and write Arabic, the ustad trains memorization of the Koran in order to foster enthusiasm in the memorization. The factor of being able to study the Koran and memorize is because of consistency and being far from technology.